Generation of an induced pluripotent stem cell (iPSC) line, DHMCi005-A, from a patient with CALFAN syndrome due to mutations in SCYL1 - Lenz, Dominic; Staufner, Christian; Wächter, Selina; Hagedorn, Maike; Ebersold, Juliane; Göhring, Gudrun; Kölker, Stefan; Hoffmann, Georg F.; Jung-Klawitter, Sabine (Stem cell research, 2019)
Variants in SCYL1 can cause a syndrome with low γ-glutamyl-transferase cholestasis, acute liver failure, and neurodegeneration (CALFAN). The encoded protein is involved in intracellular trafficking between Golgi and ER, specific mechanisms are still to be elucidated. We reprogrammed fibroblasts of a 2years old male patient with CALFAN Syndrome due to a homozygous nonsense variant in SCYL1 (c.[1882C>T]; c.[1882C>T]/p.[Gln628*]; p.[Gln628*]) and generated DHMCi005-A using the Cytotune®-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). Cells showed a normal karyotype. Pluripotency was proven using immunohistochemistry, RT-PCR, and flow cytometry. Differentiation into all germ layers was shown using the STEMdiff™ Trilineage Differentiation Kit (Stemcell Technologies).